Domestication of red fin mahseer (Tor tor) with supplementary feeds in captive condition in Bangladesh: Domestication of mahseer (Tor tor) with supplementary feeds (Journal of the Bangladesh Agricultural University, 2018)
Effects of supplementary feeds on growth, survival, and production of red fin mahseer, Tor tor (Hamilton) was assessed in captive condition under a monoculture system. Experiments were conducted for a period of 12 months where two feeds varying in protein contents were used in treatments. One laboratory formulated feed with 36.67% protein and a commercial feed with 28% protein were characterized as treatment-1 (T1) and treatment-2 (T2), respectively. At the same time water quality parameters were measured. The net increment in weight after 12 months was 671.60 g and 509.80 g in T1 and T2 respectively. The feed conversion ratio (FCR) was 4.72 and 5.26, and the specific growth rate (SGR) was 1.39 and 0.10 % day-1 in T1 and T2 respectively. In both treatments 100% fish were survived and provided the net production (kg/ha) 2807.06 and 2557.78 in T1 and T2, respectively. The water quality parameters were within the suitable range for fish culture. Between the feeds evaluated, feed with 36.67% protein (T1) proved best result considering the growth and production performance of the fish. Overall growth performance of T. tor was satisfactory; however, further research is needed.J. Bangladesh Agril. Univ. 16(3): 533–538, December 2018